Seismic activity and market efficiency : A case study of 2023 Turkish earthquakes - Büyükbozduğan, Çağrı (My University, 2024)
The occurrence of earthquakes presents a significant challenge, often resulting in high casual-ties and extensive damage. Beyond the immediate humanitarian impact, earthquakes also have far-reaching consequences for financial markets, which is seen as the barometer for economic resilience. In 2023, Türkiye experienced two earthquakes with magnitudes of 7.7 Mw and 7.6 Mw, occurring in close proximity causing a high number of casualties and eco-nomic damage. The literature remains divided on the precise effects of earthquakes on stock markets, with some studies suggesting significant negative impacts, while others find no statistically signifi-cant effects. Against this backdrop, this thesis seeks to investigate the impacts of the 2023 earthquakes on the Turkish stock market. Employing an event study methodology, the analy-sis focuses on sectoral indices and individual stock returns constituting the market index. The findings of this study reveal that while the earthquakes did not yield statistically significant results on the event day, subsequent days witnessed fluctuating effects, with returns fluctu-ating between positive and negative. Consequently, cumulative abnormal returns also failed to demonstrate statistical significance. However, studying at the sectoral level demonstrated a different picture. The results also showed that while many sectors experienced negative impacts initially, the dispersion of these effects throughout the event window was evident. Notably, sectors such as basic ma-terials and non-metal products exhibited statistically significant positive abnormal returns. On the other hand, the insurance sector emerged as particularly vulnerable, bearing statistically significant negative impacts. In conclusion, this thesis underscores the complex interplay between seismic events and financial markets, emphasizing the importance of sectoral analysis in understanding market dynamics during crises. While the overall market response may lack statistical significance, the differential impacts across sectors provide valuable insights for policymakers and inves-tors alike. Also, further research and refinement of methodologies are essential for deepen-ing our understanding of the relationship between earthquakes and financial markets.
Keywords: security market; earthquakes; financial markets; events; disasters; economic effects; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance